Climate change from the perspective of the New Public Health - Toni Buterin; Toni Buterin; Iva Rinčić; Iva Rinčić; Amir Muzur; Amir Muzur; Robert Doričić; Robert Doričić (Frontiers in Public Health)
The modern-day ecological crisis and gradual degradation of the environment, mostly due to anthropogenic effects, surpass other contemporary societal issues. Despite being largely perceived through a (bio)medical lens, the complexity of climate change as a topic is seen in different trends concerning its impact on the living world. These include historical, economic, cultural and social dimensions. Therefore, there is a need for an integrated and interdisciplinary approach resulting in more comprehensive measures to allow society to recover, but which also exploit the positive potential of climate change, through models and methods that the New Public Health can provide. Starting from the definition of the New Public Health, this paper combines and connects two topics, New Public Health and climate change, that are rarely explored together in the literature. The aim is to fill the gaps in the public health literature, where climate change is frequently viewed solely as a medical or health issue; here, we frame it as a critical challenge encompassing social, humanistic, and environmental dimensions. In addition, we offer a conceptual contribution that emphasizes their interconnection within the context of contemporary challenges.